An eighteen-month follow-up study on the effects of Intravitreal Dexamethasone Implant in diabetic macular edema refractory to anti-VEGF therapy - Pacella, Fernanda (Int J Ophthalmol, 2016)
AIM: To evaluate the long-term efficacy and safety of dexamethasone implants in subjects affected by diabetic macular edema (DME) resistant to anti-vascular endothelial growth factor (VEGF) therapy. METHODS: Thirty-two DME patients were enrolled. A 700 microgram slow release Intravitreal Dexamethasone Implant (Ozurdex(®)) was placed in the vitreous cavity. All patients were followed for 18mo. Best-corrected visual acuity (BCVA) measured with Early Treatment Diabetic Retinopathy Study (ETDRS) and central macular thickness (CMT) exams were carried out at baseline (T0) and after 1 (T1), 3 (T3), 4 (T4), 6 (T6), 9 (T9), 12 (T12), 15 (T15), and 18mo (T18) post injection. RESULTS: Repeated measures ANOVA showed an effect of treatment on ETDRS (P<0.0001). Post hoc analyses revealed that ETDRS values were significantly increased at T1, T3, T4, T9, and T15 (P<0.001) as compared to baseline value (T0). At T6, T12, and T18, ETDRS values were still statistically higher than baseline (P<0.001 vs T0). However, at these time points, we observed a trend to return to baseline conditions. ANOVA also showed an effect of treatment (P<0.0001). CMT decreased significantly at T1, T3, T4, T9, and T15 (P<0.001). At T6 (P<0.01), T12 and T18 (P<0.001) CMT was also significantly lower than T0 although a trend to return to the baseline conditions was also observed. CONCLUSION: Our findings demonstrate that Intravitreal Dexamethasone Implant is a good option to improve BCVA and CMT in DME patients resistant to anti-VEGF therapy. Our data also show that the use of drugs administered directly into the vitreous allows achieving appropriate and long-lasting concentration at the site of disease without systemic side effects.